Analysis of the Factors that Influence the Production of Rice Farming in the Pelang Rive Vilalage, Matan Subdistrict of Ketapang District - ., Anton; Yurisinthae, Erlinda; Dolorosa, Eva (Jurnal Sains Mahasiswa Pertanian, 2020)
Rice farming is food crops for the growth of rumput-berumpun need puddle. The purpose of this research is to find factors influencing the cultivation of rice farming production in the village in south river pelang former downstream, ketapang districtThe sample technique used is the method. simple random sampling The primary data ( interview ) directly to 60, respondents data on skunder pelang, river from the village office agriculture department and the statistics. ketapang districtVariables used in this research includes, area seed, fertilizer urea, , npk mkp, a herbicide, insecticides and labor.Data analysis used the, a method of linear regression and use multiple, cobb-douglas production function then processed on the spss 20 version. Based on the research done show that the use of production factors in the area, mkp and labor seeds superior significant on britain, while the seed, fertilizer urea, npk, herbicides and insecticides not significant against the production of rice fields in the river Pelang in former south Ketapang downstream district.Â Key word: rice farming production, production factor, linear regression and the worship of idols, cobb-douglassÂ